“Vse (Everyone) Online?”: an exploration of the evolution of the Russian Federation's digital government portal during the COVID-19 pandemic - Guzik, Keith (Frontiers in Sociology, 2023)
The penetration of digital technologies in government has been met with both optimism and caution. This study seeks to contribute to this field by examining how digital government evolved during the COVID-19 pandemic. Using media reports on Russia's government services portal (Gosuslugi), it finds that authorities made the portal a centerpiece of their pandemic response by enhancing its communicative, transactional, and participatory functions. These efforts aimed to not only house public health services on Gosuslugi, but to channel financial, commercial, and communication services through it, expanding Russia's digital corporatist state. While pandemic governance infused Gosuslugi with the qualities of a surveillant assemblage, it also made the portal into a space for novel forms of civic participation. Gosuslugi's evolution in this direction was limited, however, by security concerns as well as apprehension about digital participation. These findings highlight the importance of attending to political and cultural contexts in understanding digital government. In Russia, ruling elites' unwillingness to hold competitive elections and the public's lack of confidence in the political system limit the potential of digital government, regardless of its potential to manage crises.